Quantum dynamics of H(2S) + FO(2?) ? HF(1?+) + O(3P) reaction on the 13A? state - Kurban, Mustafa; Gogtas, Fahrettin; Karabulut, Ezman; Tutuk, Rukiye (Taylor & Francis Ltd, 2011)
The H(S-2) + FO((2)Pi) -> HF((1)Sigma(+)) + O(P-3) reaction on the 1(3)A` state potential energy surface is investigated using the quantum mechanical real wave packet method. The state-to-state and state-to-all reaction probabilities for total angular momentum J = 0 have been calculated. The probabilities for J > 0 have been calculated by means of the simple J-shifting method. The initial state selected integral cross-sections and rate coefficients have been calculated. The state-to-state, state-to-all reaction probabilities and the reaction cross-section do not manifest any significant oscillations and the initial state selected reaction rate constants are sensitive to the temperature.
Keywords: reaction dynamics; reactive scattering; wave packet study; real wave packet method; cross-sections